1999
DOI: 10.1001/archneur.56.11.1388
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Behavioral Responses to Cholinesterase Inhibitor Therapy in Alzheimer Disease

Abstract: Donepezil has psychotropic properties, and pretreatment behaviors help predict patients' responses to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
127
2
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 227 publications
(139 citation statements)
references
References 18 publications
5
127
2
5
Order By: Relevance
“…Hecker [18] reported improvement with donepezil in depression, anxiety, and apathy areas of the NPI when compared with placebo over 4 and 24 weeks in 191 moderate-severe AD patients. In a retrospective study in 86 AD patients Mega et al [19] observed significant improvement from baseline in delusions, agitation, anxiety, disinhibition, and irritability in responders to donepezil. The behavioral changes were dose-dependent.…”
Section: Donepezilmentioning
confidence: 98%
“…Hecker [18] reported improvement with donepezil in depression, anxiety, and apathy areas of the NPI when compared with placebo over 4 and 24 weeks in 191 moderate-severe AD patients. In a retrospective study in 86 AD patients Mega et al [19] observed significant improvement from baseline in delusions, agitation, anxiety, disinhibition, and irritability in responders to donepezil. The behavioral changes were dose-dependent.…”
Section: Donepezilmentioning
confidence: 98%
“…The study sample size was estimated based on a clinically relevant difference of 4 points on NPI, 29,30 a SD of 12 points, 31,32 and an estimated correlation with baseline of 0.6 and interclass correlation coefficient of 0.6. Approximately 130 patients were required for a power of 80% (2-sided testing at 0.05).…”
mentioning
confidence: 99%
“…In several open-label studies, donepezil treated AD patients demonstrated improvements on a variety of behavioral measures and specific behaviors such as delusions, agitation, anxiety, aggression and disinhibition. 182,183 Donepezil may also provide significant benefit for patients with LBD, especially for behaviors such as hallucinations, agitation and apathy, though certain side effects such as worsening of parkinsonism and sedation may be more common than in patients with AD. 184,185 Finally, in a large randomized placebo-controlled trial of the cholinesterase inhibitor metrifonate for mild to moderate AD, total behavioral scores improved with a significant improvement in hallucinations.…”
Section: Cholinergic Medicationsmentioning
confidence: 99%